HIV-1 CRF63_02A6 models as a tool for evaluating efficacy of developing antiretroviral drugs - D. P. Zyryanova (Infekciâ i Immunitet, 2020)
Highly active antiretroviral therapy (HAART) allows not only to control the infection process in certain patient, but also to reduce a risk of HIV infection spreading in general, so that one of the goals for international community fighting against HIV-spread is to maximize coverage of infected subjects with HAART. Antiretroviral therapy in HIV infection is administered lifelong, so that therapeutic efficacy may be lowered due to emergence of resistant HIV-1 variants. Currently, development of new antiretroviral drugs is currently underway throughout the world, therefore standard HIV-1 models are demanded to evaluate antiviral efficacy of promising drugs. To reliably assess drug efficiency regarding Russiawide HIV-1 variants, HIV-1 genovariants widespread in Russia should be used as a virus model. A recently emerged recombinant form of CRF63_02A6 HIV-1 is spread in Russia being currently a dominant variant detected among HIV-infected individuals in an extended region of the Siberian Federal District: in the Novosibirsk, Tomsk, Omsk, Kemerovo Regions, Krasnoyarsk and Altai Krai. We have obtained CRF63_02A6 infectious isolates of HIV-1, one of which contains mutations, reducing the sensitivity to the applied inhibitors of the virus reverse transcriptase. In addition, we constructed infectious molecular clones based on HIV-1 CRF63_02A6 variants with an affinity for CCR5 coreceptors and CXCR4. Infectious isolates and molecular clones CRF63_02A6 tested as models for assessing efficacy of antiretroviral drugs using the example of the drug “Efavirenz”. The fifty percent inhibitory concentration determined on the models of HIV-1 infectious molecular clones and HIV-1 isolate 18RU7056 ranged from 0.00027 pg/ml to 0.00046 pg/ml being in agreement with data published elsewhere. Concentrations of “Efavirenz” used in the study did not suppress the replication of HIV-1 12RU6987, which is resistant to non-nucleoside reverse transcriptase inhibitors, which confirms the decrease in the sensitivity of HIV-1 12RU6987 to “Efavirenz” by no less than 10,000 times. Thus, our data demonstrate that CRF63_02A6 HIV-1 isolated strains and infectious molecular clones are relevant and complementary tools for assessing efficacy of developing drugs aimed at suppressing HIV-1, including non-nucleoside-resistant virus reverse transcriptase inhibitors.